Mesenchymal stem cell-macrophage crosstalk and bone healing - Pajarinen, Jukka; Lin, Tzuhua; Gibon, Emmanuel; Kohno, Yusuke; Maruyama, Masahiro; Nathan, Karthik; Lu, Laura; Yao, Zhenyu; Goodman, Stuart B. (Biomaterials, 2019)
Recent research has brought about a clear understanding that successful fracture healing is based on carefully coordinated cross-talk between inflammatory and bone forming cells. In particular, the key role that macrophages play in the recruitment and regulation of the differentiation of mesenchymal stem cells (MSCs) during bone regeneration has been brought to focus. Indeed, animal studies have comprehensively demonstrated that fractures do not heal without the direct involvement of macrophages. Yet the exact mechanisms by which macrophages contribute to bone regeneration remain to be elucidated. Macrophage–derived paracrine signaling molecules such as Oncostatin M, Prostaglandin E2 (PGE2), and Bone Morphogenetic Protein-2 (BMP2) have been shown to play critical roles; however the relative importance of inflammatory (M1) and tissue regenerative (M2) macrophages in guiding MSC differentiation along the osteogenic pathway remains poorly understood. In this review, we summarize the current understanding of the interaction of macrophages and MSCs during bone regeneration, with the emphasis on the role of macrophages in regulating bone formation. The potential implications of aging to this cellular cross-talk are reviewed. Emerging treatment options to improve facture healing by utilizing or targeting MSC-macrophage crosstalk are also discussed.